Penerapan Metode Pembelajaran Berbasis Proyek dalam Meningkatkan Pemahaman Siswa Kelas IV Tentang Media Herbarium di Madrasah Ibtidaíyah - Fadilah, Yulina; Rizkillah, Nizrina Sofiani; Hidayat, Aji Pangestu Febrianto (IBTIDA', 2023)
The aim of this research is to improve students' creative abilities by managing plants for class 6 students in Natural Sciences material using project-based learning methods. In this study, researchers used the Classroom Action Research method. The research subjects were 6th-grade students at MI. Darul Ulum Probolinggo Regency has 11 students. From the observation results, it is stated that herbarium media can increase teacher activity, and student activity, and increase student creativity. Based on the research results, it can be concluded that herbarium media can increase creative students. The results of the skills learned by students through herbarium media from the 1st and 2nd cycles were around 95%. This shows that more than half of the students have the courage.